ANALYTIC TECHNIQUE TO DETERMINE THE ENERGY OF CONFORMAL ANTENNAS - Ibrahim, R. W; Hadid, S. B; Momani, S (university of el oued/جامعة الوادي, 2021)
The con formal mapping (CM) mode is en gaged for conformal antenna strategy using the geometric representation of the CM. For some conformal antennas (CAs) have the same shape, actuality able to segment a shared rough system, which is an essential improvement of th is method in these CA optimiza tions (CAOs). Different parameters of CAs are optimized. The function reactions in this sample are selected as starlike distribution. The assessments of efficiency, gain and accuracy with the commercial software Mathematica 11 .2 are prepared. The suggested method is mainly appropriate for CAO. Moreover, we formulate the energy operator in a 2D geometry, when the discharged field is detected over a semi circumference in the far zone.
Article
Keywords: Conformal mapping; open unit disk; starlike conformal function; c onformal antenna; energy; univalent function ; subordination and superordination